2021
DOI: 10.1097/aud.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Relationship Between Speech Recognition in Noise, Need for Recovery After Work, Job Demand, and Job Control Over a Period of 5 Years

Abstract: Hearing impairment may lead to an increased need to recover from fatigue and distress after a day of work. Also, hearing impairment may negatively affect the balance between workload and control over it (job demand and job control). The uptake of hearing solutions may have a positive effect on these outcomes. We aimed to assess the longitudinal relationship between change in speech recognition in noise and changes in need for recovery after work and job demand and job control, and the influence of hearing solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Especially, interventions that affect personal adjustments may be promising to reduce NFR in employees with hearing loss. As suggested in previous studies (Backenroth-Ohsako et al 2003;Gussenhoven et al 2017;van Leeuwen et al 2021), we therefore hypothesize that greater improvement in NFR might be obtained when sensory management interventions are not provided in isolation, but combined with interventions that foster adequate coping behavior. Future research is required to assess this hypothesis, since no conclusions on causality can be drawn because of the design of this study.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Especially, interventions that affect personal adjustments may be promising to reduce NFR in employees with hearing loss. As suggested in previous studies (Backenroth-Ohsako et al 2003;Gussenhoven et al 2017;van Leeuwen et al 2021), we therefore hypothesize that greater improvement in NFR might be obtained when sensory management interventions are not provided in isolation, but combined with interventions that foster adequate coping behavior. Future research is required to assess this hypothesis, since no conclusions on causality can be drawn because of the design of this study.…”
Section: Discussionmentioning
confidence: 74%
“…Our study is the first that demonstrates that the NFR of employees with hearing loss can be improved by aural rehabilitation. In previous studies, no significant improvement in NFR was reported after aural rehabilitation (Gussenhoven et al 2017;van Leeuwen et al 2021). An explanation might be that the population of Gussenhoven et al ( 2017) included a relatively high number of participants with low NFR, which might have resulted in a floor effect in their study.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations